COMMUNITY EMPOWERMENT THROUGH TOURISM-BASED MANAGEMENT LOCAL WISDOM IN SERVICE COOPERATIVES “BOONPRING MAKMUR SEJAHTERA” - Sulistyo, Sulistyo; Manik, Yuni Mariani; Yogivaria, Doni Whirsandono (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
By the end of 2019, the Covid-19 virus had spread throughout the world, including Indonesia. The government immediately imposed Large-Scale Social Restrictions (PSBB) in several big cities in Indonesia. PSBB has a direct impact on the MSME sector. MSMEs experienced a decline in sales turnover due to restrictions on physical activities. This makes MSMEs lose the opportunity to sell their products through exhibitions, bazaars, car free days and others. One of the most affected is the “Boonpring Makmur Sejahtera” Cooperative which houses wood & bamboo craftsmen in Malang Regency. The area of   Sanankerto Village, Turen District, Malang Regency has the potential for rural tourism that has the potential to be developed. This village has interesting natural characteristics, unique social and cultural life. This potential must be encouraged and developed in accordance with the socio-cultural characteristics of the community. The development of community-based tourism potential is a strategic effort in building the community. Rural tourism development is a long-term and potential investment for the government because human and natural resources are already available. The results of our brief observations found that the sales of the Boonpring Makmur Sejahtera Cooperative decreased drastically, even to the point that there were no purchases at all. The Boonpring Makmur Sejahtera Cooperative and members of the cooperative personally then try to market their products online through social media. It turned out that the members of the cooperative experienced many difficulties and obstacles in online marketing, so many gave up. This service activity is expected to motivate the management and members of the Boonpring Makmur Sejahtera Cooperative to remain creative, productive and aggressive. This service activity involves a series of activities, namely: providing motivation to cooperative management and members, online marketing training and easy and practical bookkeeping training with applications. Service participants (management and members of the Boonpring Makmur Sejahtera Cooperative) in participating in the training were very enthusiastic and diligent. The material provided by several competent personnel was well received and practiced so as to give encouraging results. Although the pandemic is still ongoing, the Boonpring Makmur Sejahtera Cooperative is slowly starting to rise and exist again so that wood & bamboo craftsmen become empowered again.